Analysis of Informal Obstacles to Cross-Border Economic Activity in Kazakhstan and Uzbekistan - Roman Vakulchuk; Farrukh Irnazarov (Asian Development Bank (ADB), 2014)
The barriers to trade in developing countries constitute one of the major obstacles to economic development and growth. This study aims at addressing the issues surrounding the prevalence of informal trade barriers in Kazakhstan and Uzbekistan. While it appears to be logical that the strongest economies of Central Asia should increase trade volume with neighboring countries, in reality the potential for intensifying cross-border trade is barely being realized. This paper attempts to shed light on trade barriers in key industries in both countries, including manufacturing, transport, and agriculture. As can be seen from this study, these industries experience different types of restrictions and varying degrees of state intervention in Kazakhstan and Uzbekistan. The paper places special emphasis on informal barriers and the tools companies use to overcome those barriers. The paper is based on a survey of a total of 108 companies in both countries and the output of a roundtable discussion in Kazakhstan with representatives of companies and other experts in the above-mentioned industries.
hdl:11540/1291
Keywords: D80; F10; F20; L10; L20; 330; Kazakhstan; Uzbekistan; trade; formal and informal barriers; cross-border activity